Mechanisms of early Drosophila mesoderm formation. - Leptin, M.; Casal, J.; Grunewald, B.; Reuter, R. (Gastrulation, 1992)
Several morphogenetic processes occur simultaneously during Drosophila gastrulation, including ventral furrow invagination to form the mesoderm, anterior and posterior midgut invagination to create the endoderm, and germ band extension. Mutations changing the behaviour of different parts of the embryo can be used to test the roles of different cell populations in gastrulation. Posterior midgut morphogenesis and germ band extension are partly independent, and neither depends on mesoderm formation, nor mesoderm formation on them. The invagination of the ventral furrow is caused by forces from within the prospective mesoderm (i.e. the invaginating cells) without any necessary contribution from other parts of the embryo. The events that lead to the cell shape changes mediating ventral furrow formation require the transcription of zygotic genes under the control of twist and snail. Such genes can be isolated by molecular and genetic screens.